Implemention of direct sequence spread spectrum modulation in RS-232 transceiver [microfilm] - Gan, Hock Lai (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2002